(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
In urban locations around the world, traffic congestion is a problem. Congestion has increased as a result of inadequate public transportation, stalled development of the road infrastructure, and increased use of private transportation by the public to meet the demand for travel. In developing nations like India, the issue has become more complex due to heterogeneous traffic on subpar road and control conditions. Travel delays and greater vehicle emissions are a result of traffic congestion. In developed nations, studies have been done to quantify congestion in order to assess the current condition and project possible future scenarios. Planning for extra infrastructure facilities and initiatives needed to reduce congestion has been done successfully using these strategies. The current explanations for the congestion caused by the varied traffic conditions used in India are insufficient. Due to the set PCE values used for the vehicles and the capacity norms provided for urban roads, the widely used v/c ratio and LOS to evaluate the quality of travel in urban environments have some limitations. The goals of the current study are to develop a mathematical model to calculate traffic congestion for heterogeneous traffic as well as to assign LOS to the studied route segments. Data collecting involves the use of video graphic techniques. On the Jahangir Chowk–Skims Soura length, several sections have been designated for study. By taking the pertinent information out of the digital video clip, the traffic’s characteristics have been examined.